Characterization of the adaptive immune response in a mouse model for HPV-positive head and neck squamous cell carcinoma with implications to human disease - Franziska Oliveri; Linda Neher; Ronja Pscheid; Isabel Sewald; Sowmya Gowdavally; Annika C. Betzler; Jaqueline Hallitsch; Jens Greve; Simon Laban; Sebastian Schmid; Thomas K. Hoffmann; Patrick J. Schuler; et al. (Cancer Immunology, Immunotherapy)
Abstract Head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer worldwide with a poor prognosis for survival. Risk factors include alcohol and tobacco abuse and infection with human papilloma virus (HPV). To enhance anti-tumor immune responses immunotherapeutic approaches are approved for recurrent metastatic disease but only approx. 20% of patients respond to checkpoint blockade of the PD-1/PD-L1 axis. Therefore, preclinical research is needed to better understand molecular and cellular processes and to identify new therapeutic targets. Immunocompetent mouse models can serve these purposes but only few are currently available for HPV-positive HNSCC. Here, we established a mouse cell line overexpressing the oncogenes E6/E7 of the HPV16 genome as well as a constitutively active form of H-Ras and studied the anti-tumor immune response upon orthotopic tumor growth at the floor of the mouth. Moreover, we analyzed the same immunoregulatory pathways in samples of HPV-positive cancer patients. T cells in the tumor of mice and humans exhibited high expression of CD39 and CD73, two ectoenzymes involved in the production of immunosuppressive adenosine from ATP, along with increased expression of PD-1, LAG-3 and GITR. Additionally, B cell responses were elevated in tumor-bearing mice, seen as an increase of germinal center, immunoregulatory marginal zone and follicular B cell subtypes. Taken together, this study suggests that the generated mouse model shares characteristics with human disease and can thus be used as a platform to study anti-tumor responses in HPV-positive HNSCC which will help to identify novel therapeutic targets.